Impact of CPO export duties on Malaysian palm oil industry - Abdulla, Ibragimov; Mohamed Arshad, Fatimah; Bala, Bilash Kanti; Mohd Noh, Kusairi; Muhammad Tasrif, (Science Publications, 2014)
In January 2013, Malaysia reduced the export duty structure to be in line with the Indonesia's duty structure. Both countries export crude and processed palm oil. Since Malaysia and Indonesia are close competitors and they compete in the same market, a change in export duty rate in one country will affect the other. Indonesia, as the world's biggest palm oil producer, has drastically widened the values between the crude palm oil and refined palm oil export taxes since October 2011, to encourage more downstream investments and production of refined palm oil products. Under the revised export duty structure, crude palm oil and crude palm kernel oil are cheaper for downstream activities in Indonesia. The new structure is expected to reduce Malaysia's competitiveness in the world market as its export duty is relatively higher. A high export duty results in high price of crude palm oil which is the raw material for processed palm oil. The research questions are: (i) What are the likely future trends of crude palm oil exports under the new crude palm oil export duties? Will it increase, reduce or stabilize? (ii) What are the likely future trends of processed palm oil exports? Will it increase exponentially, stabilize or reduce? To answer these questions, a system dynamics model was developed for the Malaysian palm oil. Application of the system dynamics model provides a framework to understand the feedback structure and how changes in variables impact the behavior of the palm oil industry. This research suggests that with low crude palm oil export duties crude palm oil domestic price, profitability of plantation owners, immature crop, mature crop, total planted area, production and exports of crude palm oil increase, however exports of processed palm oil decrease.